Survey on Chlamydophila psittaci in captive ramphastids in São Paulo State, Brazil - Raso, Tania de Freitas; Ferreira, Vivian Lindmayer; Friciello Teixeira, Rodrigo Hidalgo; Augusto Pinto, Aramis [UNESP] (Universidade Federal de Santa Maria (UFSM), 2012)
Chlamydophila psittaci (C. psittaci) has been detected in 460 avian species, among them the most frequent are the Psittaciformes, Columbiformes, Anseriformes and raptors. In Brazil, the main avian species recognized as healthy carriers belong to the order Psittaciformes and Columbiformes, but very few studies have been done in other bird families. Reports of the occurrence of this disease in the clinical form are rare in the Ramphastids; consequently, they are not commonly evaluated for this agent. The present study reports the investigation of C. psittaci in 25 captive ramphastids from a zoological park in São Paulo State, Brazil. Swabs samples from the cloaca were submitted to semi-nested polymerase chain reaction (semi-nested PCR) for direct detection of the microorganism. Additionally, blood samples obtained from these birds were submitted to the Complement Fixation Test (CFT) for detection of antibodies anti-C. psittaci. The presence of C. psittaci was not detected in the cloacal swab samples tested by the PCR. Nevertheless, 16% (4/25) of the bird's sera were positive by the CFT. Among the species with positive results, there are the saffron toucanet (Pteroglossus bailloni) and black-necked-aracari (Pteroglossus aracari), two species with no descriptions of the survey of C. psittaci published in the literature. Intermittent elimination of C. psittaci is a feature of chronically infected birds; however the absence of a positive-antigen sample did not guarantee that the bird is Chlamydophila-free. The serological results obtained show that the ramphastids tested were previously exposed to the pathogen and developed immune response, but showed no clinical signs of the disease and didn't eliminate regularly the organism in their feces in the moment of the sample collection.

Chlamydophila psittaci (C. psittaci) tem sido detectada em 460 espécies aviárias, dentre elas, as mais frequentes são os Psitaciformes, Columbiformes, Anseriformes e Falconifomes. No Brasil, as principais espécies reconhecidas como portadoras pertencem às Ordens Columbiformes e Psitaciformes, porém poucas pesquisas foram realizadas em aves de outras famílias. Em ranfastídeos, são raros os relatos da ocorrência da forma clínica dessa doença, consequentemente, não é um patógeno comumente investigado. O presente estudo relata a investigação de C. psittaci em 25 ranfastídeos cativos em um parque zoológico de São Paulo. Amostras de suabes colhidas da cloaca foram submetidas à reação em cadeia pela polimerase (PCR) para detecção direta do microrganismo. Adicionalmente, amostras de soro sanguíneo obtidas dessas aves foram submetidas à reação de Fixação do Complemento (RFC) para detecção dos anticorpos anti-C. psittaci. Não foi detectada a presença de C. psittaci em nenhuma das amostras de suabe cloacal testadas pela PCR. No entanto, 16% (4/25) das amostras de soros foram positivas pela RFC. Entre as espécies com resultados positivos, estão o araçari-banana (Pteroglossus bailloni) e o araçari-de-bico-branco (Pteroglossus aracari), ambas sem publicações prévias relacionadas à C. psittaci. A eliminação intermitente de C. psittaci é uma característica de aves cronicamente infectadas, porém um resultado negativo para pesquisa do agente não significa necessariamente que a ave esteja livre do patógeno. Os resultados sorológicos obtidos demonstram que algumas aves tiveram contato prévio com o microrganismo e desenvolveram resposta imune, porém não apresentavam sinais clínicos evidentes de doença e não eliminavam o agente etiológico no momento da colheita da amostra.
Pesquisa de Chlamydophila psittaci em ranfastídeos cativos no Estado de São Paulo, Brasil
Keywords: Aracaris; Chlamydiosis; Chlamydophila psittaci; Ramphastids; Toucans